Hazard Control Working at Height at PT Wijaya Karya Bangunan Gedung Tbk. Halim High-Speed Train Construction Project - Madhona, Yenny Frisca; Handayani, Hanifah; Khairunisa, Sri Dinda (Riviera Publishing, 2024)
PT Wijaya karya Bangunan Gedung Tbk. Halim High-Speed Train Project is a company engaged in construction, investment, and concessions. Engaged in the construction sector certainly has a high potential for danger and danger factors. One of them was an accident caused by working at a height. Therefore, it is important to control the danger of working at height to prevent and control the danger of height. This study uses field observation methods, literature studies, and interviews to determine how the hazard control program works at height. The hazard control program for working at height at PT Wijaya Karya Bangunan Gedung Tbk, Halim High-Speed Train Project has been by the regulation of the Minister of Manpower No. 9 of 2016, among others. Fit to work, toolbox meeting inspection, Scaffolding and Full Body Harness. At PT Wijaya Karya Bangunan Gedung Tbk, The halim high-speed train project has procedures related to the Control of work hazards at height, namely the height work safety procedure No. WIKA-BG-PDSMM-IK-26. PT Wijaya Karya Bangunan Gedung Tbk. Halim High-Speed Train Project, but there are still problems related to the lack of supervision of work safety equipment and lack of training for workers related to high-altitude work.